2011
DOI: 10.1682/jrrd.2010.08.0140
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of driving difficulties in Operation Iraqi Freedom/Operation Enduring Freedom combat returnees

Abstract: Abstract-We studied the prevalence and characteristics of selfreported driving difficulties and examined their association with traumatic brain injury (TBI) and/or posttraumatic stress disorder (PTSD) in Operation Iraqi Freedom/Operation Enduring Freedom (OIF/OEF) veterans who were seen at a Department of Veterans Affairs outpatient polytrauma clinic. In this study, we used a brief driving questionnaire and chart reviews to assess the prevalence and characteristics of driving difficulties in the following four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 54 publications
6
48
0
Order By: Relevance
“…These observations have been supported by prior literature on Veterans with PTSD, which has shown that post-9/11 Veterans with PTSD are more likely than those who screen negative for PTSD to report aggressive driving and more persistent driving problems [6,14], and they are four times more likely to report anxiety and hyperarousal on the road [4]. Amick et al also reported that combat Veterans with comorbid PTSD and mild TBI make more critical errors while driving in a simulated environment than nondisabled control subjects [6].…”
Section: Combat Veterans Of Iraq and Afghanistan (Operation Iraqi Fresupporting
confidence: 68%
See 2 more Smart Citations
“…These observations have been supported by prior literature on Veterans with PTSD, which has shown that post-9/11 Veterans with PTSD are more likely than those who screen negative for PTSD to report aggressive driving and more persistent driving problems [6,14], and they are four times more likely to report anxiety and hyperarousal on the road [4]. Amick et al also reported that combat Veterans with comorbid PTSD and mild TBI make more critical errors while driving in a simulated environment than nondisabled control subjects [6].…”
Section: Combat Veterans Of Iraq and Afghanistan (Operation Iraqi Fresupporting
confidence: 68%
“…Many of the high-risk behaviors endorsed by our sample (e.g., speeding, accelerating through yellow lights, becoming easily distracted by sights and sounds) have been reported in prior studies on Veterans [2,14]. However, several protective behaviors were also highly endorsed by this sample (e.g., wearing a seatbelt or helmet, using a designated driver), and this finding likely to wear seatbelts and more likely to drive intoxicated than noncombat Veterans [8,[22][23].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies using survey or self-report methods, and including returning OIF/OEF Veterans, have identified aggressive, unsafe, or dangerous driving as issues for those with PTSD [13], TBI [3], or both conditions [4][5]11,[14][15]. TBI leads to cognitive, physical, behavioral, emotional, visual, and perceptual deficits [16], which can result in unsafe vehicle operation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Normal hearing, vision, and balance and coordination are important for performing activities of daily living, psychosocial functioning, leisure activities, and employment [7,[37][38][39][40][41][42] and are necessary for communication and rehabilitation. A growing literature suggests auditory, visual, and vestibular symptoms are common among OIF/OEF veterans who have experienced TBI, but no studies to date have examined the coexistence of these symptoms in a large cohort.…”
Section: Introductionmentioning
confidence: 99%